GIS BASED WATER MANAGEMENT EFFICIENCY ATTEMPT IN WATER USERS ASSOCIATIONS LOCATED IN SOUTH FERGHANA CANAL BASIN (Journal of Geography and Environmental Management, 2016)
Efficient water use is the important issue in Uzbekistan. The Ferghana valley with the high density of population always faces lack of water resources for irrigation. Therefore, it is a challenging issue for the water management organizations to use advanced information technologies such as GIS and Remote Sensing in carrying out inventory on real conditions of irrigation and drainage canals, hydro technical facilities in respective areas. Current article investigates the possibility of using such advanced technologies in creation of data base and GIS maps by use of ArGIS 9.3 software and outlines future impact to the maintenance of the hydro technical facilities. The paper explains the methods of data processing and subsequently developing spatial data base for the water facilities that will enable for the users to make query and further updating, changing works on given GIS maps.